Essentials of Business Budgeting - Finney, Robert G. (New York American Management Association, 1995)
Now readers can acquire the budgeting know-how needed to master the budgeting process--without an accounting background. This concise guide provides readers with all the skills they need to participate in the budgeting process and turn it into a powerful decision-making tool.
Include Glossary
Keywords: Budget in business -- Business